Answer :

a2b2x2 + b2x - a2x - 1 = 0

b2x(a2x + 1) - 1(a2x + 1) = 0 taking b2x common from first two terms and - 1 from last two


(a2x + 1) (b2x - 1) = 0


(a2x + 1) = 0 or (b2x - 1) = 0



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses